Never too early: the impact of a shadowing programme in paediatric and congenital cardiac surgery for undergraduate college students. (April 2023) - Brennan, Zachary; Purlee, Matthew; Sharaf, Omar M.; Badhwar, Isabella E.; Brown, Colton; Kugler, Liam; Weinstein, Douglas J.; Bassuk, Jonah S.; Baydoun, Yasmine; Neal, Dan; Stukov, Yuriy; Freeman, Kirsten; et al.
Abstract: Purpose: Diversification of the medical and cardiothoracic surgical workforce represents an ongoing need. A congenital cardiac surgery shadowing programme for undergraduate students was implemented at the University of Florida Congenital Heart Center. Methods: Students shadowing in the Congenital Heart Center from 17 December 2020 through 20 July 2021 were sent a survey through Qualtrics to evaluate the impact of their shadowing experience. The main objectives of the survey were to determine the personal relationship(s) of the students to physicians prior to shadowing, how the presence or absence of physicians in the family of a given student related to the exposure of the student to a medical setting prior to shadowing, and the interest of the students in medicine and cardiothoracic surgery prior to and after the shadowing experience. Survey responses included "Yes/No" questions, scaled responses using a Likert scale, selection lists, and free text responses. When applicable, t-tests were utilised to assess differences between student groups. Results: Of the 37 students who shadowed during the study period, 26 (70%) responded. Most students were female (58%, n = 15), and the mean age was 20.9 ± 2.4 years. Students spent a mean duration of 95 ± 138 hours shadowing providers as part of the shadowing programme. Likert scale ratings of interest in the professions of medicine, surgery, and cardiothoracic surgery all increased after the shadowing experience (p < 0.01). Students with a family member in medicine had more clinical exposure prior to the shadowing programme (p < 0.01). Conclusion: A surgical shadowing programme at a Congenital Heart Center may have an important formative impact on the views of undergraduate students regarding potential careers in surgery and medicine. Additionally, students without family members in medicine tend to have less prior exposure to medicine and could likely benefit more from this type of shadowing programme.